961. Implementing an HIV Ambulatory Curriculum in Internal Medicine Residency Programs. (31st December 2020) - Aoun-Barakat, Lydia; McKay, Sharen E; Danvers, karina; Sideleau, Robert J; Brooks, Ralph P; Villanueva, Merceditas
Abstract: Background: The advancement of anti-retroviral therapy (ART) has transformed HIV into a chronic disease and resulted in prolonging the lives of people living with HIV. Therefore, there is a projected shortage of HIV providers nationally and there is a need for increased training of primary care physicians in management of HIV over the lifespan as well as alongside common comorbidities found in aging HIV population. Methods: The Yale AIDS program developed an interactive HIV ambulatory curriculum that included a set of didactics and workshops for trainees in internal medicine residency programs. This 3-hour interactive curriculum was implemented in 5 hospitals in Connecticut and was led by experienced HIV providers at the MD and RN levels. Trainees included PGY1, 2 and 3 residents. Knowledge areas encompassed HIV Epidemiology, Testing, ART Treatment, and prevention including Pre Exposure Prophylaxis (PrEP). In addition, 2 role-play sessions were integrated. Pre and Post Test knowledge assessment was evaluated including questions on practice regarding HIV screening and PrEP prescribing. Results: In this study, we report the results of knowledge assessments and professional practices administered prior to (pre-) and following (post-) interactive learning sessions. From July 2017 to June 2020, 15 HIV ambulatory curriculum sessions were held, with an average 5 sessions annually. A total of 170 residents attended this curriculum with an average of 10-15 trainees per session and 25% from underrepresented minority group. The pre-test and the post- test knowledge assessment score rates were 51% and 83% respectively with an estimated 63% improvement. A large proportion of trainees reported implementing routine HIV testing (97.2%). However, self-reported willingness to prescribe PrEP was low among residents prior to the educational intervention (12.5%) and increased considerably following education (93.3%). Conclusion: Focused interactive HIV curriculum could represent a viable method to improve knowledge and practices in HIV medicine amongst primary care residents. This novel educational intervention has the potential to be disseminated an implemented in other residency programs curricula. Disclosures: All Authors : No reported disclosures